Single‐Atom Sites on MXenes for Energy Conversion and Storage. Issue 6 (7th May 2021) - Cui, Yanglansen; Cao, Zhenjiang; Zhang, Yongzheng; Chen, Hao; Gu, Jianan; Du, Zhiguo; Shi, Yongzheng; Li, Bin; Yang, Shubin
Abstract : Single‐atom sites on MXenes (SASs‐MXenes) have attracted widespread attention for energy storage and conversion due to their highest atom utilization efficiency, intriguing intrinsic properties, unusual performance, and improved robustness. In addition, the large surface area and abundant anchor sites make MXenes ideal substrates for supporting single atoms via covalent interaction. Herein, the main strategies for synthesis of SASs‐MXenes are first summarized, which cover capturing single atoms by cation vacancies, coordinating single atoms with heterodopants, and inheriting single atoms from MAX phases. Then, disclosing the crucial roles SASs‐MXenes play in tuning the kinetics and thermodynamics of various catalytic reactions, i.e., hydrogen evolution reaction, nitrogen reduction reaction, CO2 reduction reaction, CO2 functionalization, polysulfide conversion, and other redox reactions involved in rechargeable batteries, is focused on. Finally, the challenges and future opportunities for developing highly active SASs‐MXenes are discussed. Abstract : Single‐atom sites on MXenes (SASs‐MXenes) show great potentials in various energy conversion and storage applications due to their unique electronic structures and tunable coordination environments. Herein, the synthetic strategies for SASs‐MXenes are summarized and their essential roles in these energy‐related reactions are revealed. Finally, the challenges and prospects to develop high‐performance SASs‐MXenes are presented.